MXene−Graphene Oxide Heterostructured Films for Enhanced Metasurface Plasmonic Biosensing in Continuous Glucose Monitoring - Rui Li; Hongli Fan; Youqian Chen; Shaoping Yin; Gang L. Liu; Yanan Li; Liping Huang (Advanced Science)
Abstract Non‐invasive biosensors have attracted attention for their potential to obtain continuous, real‐time physiological information through measurements of biochemical markers, such as one of the most important—glucose, in biological fluids. Although some optical sensing materials are used in non‐invasive devices for continuous glucose monitoring (CGM), surface or localized plasmon sensing material are seldom applied in CGM owing to modest sensitivity and bulk sensing apparatus. Herein, a metasurface (MGMSPR) biosensor based on the metasurface plasmon resonance chip modified with heterostructured Ti3C2 MXene−Graphene oxide (MG) is reported, which potentially enables ultra‐sensitive glucose detection. The sensor consists of a dual‐channel microfluidic device integrated with silver mirror enhanced MGMSPR chips. Not only does it promote the entry of glucose oxidase (GOD) into the internal pores and enhance the stable fixation of GOD in the membrane, but also the integration of MG material provides a high specific surface area and unique electronic properties, thereby significantly enhancing the sensitivity of the MGMSPR sensor. The detection limit of MGMSPR biosensor is 106.8 µM. This pioneering approach opens new avenues for monitoring physiological parameters and process analytical technology on an optical platform, providing continuous health monitoring and production process control through optical sensors.